Effectiveness and Characteristics of Interactive E-Modules in Physics Learning in The Merdeka Curriculum: A Systematic Literature Review (2022–2025) - Alia Cahyani; Ziadatun Nikmatillah; Maria Anastasia Da Lopez; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2026)
The development of technology in education encourages the use of more interactive digital learning materials, one of which is the e-module. This study aims to analyze the effectiveness and characteristics of interactive e-modules in physics learning within the Merdeka Curriculum. This research uses a Systematic Literature Review (SLR) method with the PRISMA guidelines. The data sources were obtained from articles indexed in Google Scholar from 2022 to 2025 using the Publish or Perish application. The selection process was conducted based on inclusion and exclusion criteria, resulting in 16 relevant articles for analysis. The results of the review show that interactive e-modules are generally developed using various learning models such as Problem Based Learning, STEM-integrated Project Based Learning, SETS, and contextual learning. The e-modules are also equipped with interactive features such as animations, videos, simulations, quizzes, and virtual laboratories that can increase student engagement. Based on the analyzed studies, the use of e-modules has been proven effective in improving learning outcomes, motivation, and students’ critical and creative thinking skills. Therefore, interactive e-modules have great potential to support more effective and innovative physics learning in the implementation of the Merdeka Curriculum.